Effects of Sigh on Regional Lung Strain and Ventilation Heterogeneity in Acute Respiratory Failure Patients Undergoing Assisted Mechanical Ventilation*. Issue 9 (September 2015) - Mauri, Tommaso; Eronia, Nilde; Abbruzzese, Chiara; Marcolin, Roberto; Coppadoro, Andrea; Spadaro, Savino; Patroniti, Nicolo'; Bellani, Giacomo; Pesenti, Antonio
Abstract : Objective: In acute respiratory failure patients undergoing pressure support ventilation, a short cyclic recruitment maneuver (Sigh) might induce reaeration of collapsed lung regions, possibly decreasing regional lung strain and improving the homogeneity of ventilation distribution. We aimed to describe the regional effects of different Sigh rates on reaeration, strain, and ventilation heterogeneity, as measured by thoracic electrical impedance tomography. Design: Prospective, randomized, cross-over study. Setting: General ICU of a single university-affiliated hospital. Patients: We enrolled 20 critically ill patients intubated and mechanically ventilated with PaO2 /FIO2 up to 300 mm Hg and positive end-expiratory pressure at least 5 cm H2 O (15 with acute respiratory distress syndrome), undergoing pressure support ventilation as per clinical decision. Interventions: Sigh was added to pressure support ventilation as a 35 cm H2 O continuous positive airway pressure period lasting 3–4 seconds at different rates (no-Sigh vs 0.5, 1, and 2 Sigh(s)/min). All study phases were randomly performed and lasted 20 minutes. Measurements and Main Results: In the last minutes of each phase, we measured arterial blood gases, changes in end-expiratory lung volume of nondependent and dependent regions, tidal volume reaching nondependent and dependent lung (Vtnondep and Vtdep ), dynamic intratidal ventilation heterogeneity, defined as the average ratio of Vt reaching nondependent/Vt reaching dependent lung regions along inspiration (VtHit ). With Sigh, oxygenation improved ( p < 0.001 vs no-Sigh), end-expiratory lung volume of nondependent and dependent regions increased ( p < 0.01 vs no-Sigh), Vtnondep showed a trend to reduction, and Vtdep significantly decreased ( p = 0.11 and p < 0.01 vs no-Sigh, respectively). VtHit decreased only when Sigh was delivered at 0.5/min ( p < 0.05 vs no-Sigh), while it did not vary during the other two phases. Conclusions: Sigh decreases regional lung strain and intratidal ventilation heterogeneity. Our study generates the hypothesis that in ventilated acute respiratory failure patients, Sigh may enhance regional lung protection. Abstract : Supplemental Digital Content is available in the text.